2007
DOI: 10.1007/s00392-007-0618-5
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-eluting stents in the treatment of chronic total coronary occlusions

Abstract: Implantation of the Cypher stent reduces the restenosis rate and seems to be a safe and effective tool for the treatment of chronic total coronary occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Therefore, the authors concluded that there is no evidence that immediate (\30 days) ICD implantation after myocardial infarction improves mortality. (Presenter: D. Andresen, Berlin) GERSHWIN Percutaneous coronary intervention using sirolimuseluting stents (SES) has been shown to reduce instent-restenosis compared to bare metal stents (BMS) [2]. The objective of the GERSHWIN (German stent health outcome and economics within normal practice) study was to study clinical benefit (MACE: death, myocardial infarction, bypass therapy, re-PCI in the target vessel), costs, and quality of life using SES or BMS [3] Death from ischemic heart diseases (ICD-10 I20-I25), consisting largely of acute myocardial infarction (I20) and chronic ischemic heart disease (I25) showed strong regional variation with high figures ([155 cases per 100,000 men) in the north-east and the Saarland, and \100 cases in the south, particularly in the south-west of Germany.…”
Section: Irismentioning
confidence: 99%
“…Therefore, the authors concluded that there is no evidence that immediate (\30 days) ICD implantation after myocardial infarction improves mortality. (Presenter: D. Andresen, Berlin) GERSHWIN Percutaneous coronary intervention using sirolimuseluting stents (SES) has been shown to reduce instent-restenosis compared to bare metal stents (BMS) [2]. The objective of the GERSHWIN (German stent health outcome and economics within normal practice) study was to study clinical benefit (MACE: death, myocardial infarction, bypass therapy, re-PCI in the target vessel), costs, and quality of life using SES or BMS [3] Death from ischemic heart diseases (ICD-10 I20-I25), consisting largely of acute myocardial infarction (I20) and chronic ischemic heart disease (I25) showed strong regional variation with high figures ([155 cases per 100,000 men) in the north-east and the Saarland, and \100 cases in the south, particularly in the south-west of Germany.…”
Section: Irismentioning
confidence: 99%
“…Percutaneous coronary intervention using sirolimus-eluting stents (SES) has been shown to reduce in-stent-restenosis compared to bare metal stents (BMS) [2]. The objective of the GERSHWIN (German stent health outcome and economics within normal practice) study was to study clinical benefit (MACE: death, myocardial infarction, bypass therapy, re-PCI in the target vessel), costs, and quality of life using SES or BMS [3].…”
Section: Gershwinmentioning
confidence: 99%